Kerja Kode Dalam Meme Soeharto - Rizky Noviasri (Aliansi Desainer Produk Industri Indonesia (ADPII), 2019)
One of the communication phenomena on the internet is the emergence of Suharto memes. Meme Soeharto is commonly known by the visualization of Suharto waving his hand with a smile accompanied by the words